Population status and conservation of the threatened and endemic tree Vatica javanica subsp. javanica (Dipterocarpaceae) - Rizmoon Nurul Zulkarnaen; Hendra Helmanto; Enggal Primananda; Yayan Wahyu Candra Kusuma; Iyan Robiansyah (Journal of Asia-Pacific Biodiversity, 2023)
Vatica javanica subsp. javanica is only found in Ciangir and Halimun in West Java, Indonesia. A ≥20-year-old evaluation led to the designation of the subspecies as Critically Endangered. Furthermore, the subspecies is currently not present in ex situ collections. To enhance the conservation of the species, in the present study, we conduct population surveys and plant materials collection. With a total of 625 individuals, we were able to locate the subspecies in both locations by using a concentrated survey strategy. The extent of occurrence and area of occupancy of the subspecies were 16.26 km2 and 12 km2, respectively. The populations in both sites were dominated by individuals with dbh <5 cm. Only 45 mature specimens were seen during the surveys. The habitats of the subspecies were characterized by humid and moderate acidic soil, slope topography, and northerly aspects. A total of 125 seedlings were successfully raised from the seeds and are being grown in the Bogor Botanic Gardens as ex situ collections. Based on our research, we propose the category of Critically Endangered (CR) D as the new conservation status of the subspecies. Habitat conversion and degradation were observed to be the main threats to the subspecies. Increasing the protection level of the habitats is urgently needed.